Pengaruh Health Education Vulva Hygiene Dengan Audio Visual Dan Media Cetak (Booklet) Terhadap Pengetahuan Tentang Fluor Albus Pada Remaja di Pondok Pesantren Al Muhajirin 2 Tambakberas Jombang - Eka Sofia Larasati; Erna Ts; Faishol Roni; Leo Yosdimyati; Tiara Fatma Pratiwi (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract Vaginal discharge is one of the reproductive health problems experienced by young women. the causes and prevention of vaginal discharge which, if not treated properly, can be fatal.This study aims to determine the effect of health education on vulva hygiene using audiovisual and print media on knowledge about preventing fluoride in adolescents at Pondok Al Muhajirin 2 Tambakberas Jombang. The type of research used was pre-experimental using a "one-group pretestposttest design" approach. The population in this study were students of Al Muhajirin Islamic Boarding School 2 Tambak Rice Jombang in 2024 aged 10-19 years, totaling 52 children. The research instrument used was a questionnaire with audiovisual research methods and print media (booklets). The statistical test in this study used the Wilcoxon Test. The results of statistical tests using the Wilcoxon test with a significance value of p value = 0.000 < 0.05 means that H1 is accepted, which means there is an influence of health education on vulva hygiene with audiovisual and print media on knowledge about preventing fluor albus in adolescents. The results of the research show that there is an influence of health education on vulva hygiene with audiovisual and print media on knowledge about preventing fluoride in adolescents at Pondok al Muhajirin 2 Tambakberas Jombang. It is hoped that future researchers can use a larger sample size and utilize new information media. Keywords: health education, level of knowledge, fluor albus